CORRELATION BETWEEN PERSONALITY TYPE AND SHIFT WORK WITH ANXIETY LEVEL ON NURSES IN EMERGENCY ROOM (ER) AND PSYCHIATRIC INTENSIVE CARE UNIT (PICU) MENTAL HOSPITAL IN YOGYAKARTA - Yulia Dwi Andarini; Widya Fatmawati (Universitas Darussalam Gontor, 2018)
Background. Hospital is included in the criteria of workplace with various health hazards, especially for the people who work in hospital. Anxiety is one of health problem faced by workers in hospital. Anxiety is a condition with the feeling of worrying which somatic symptom can be persist also, that may influence occupational health and safety. Nurses in hospital work with shift system which has many negative effect to the health. One of those negative effect is anxiety. There are many factors that can influence anxiety, these factor is for example personality types.Objective. This study aims to determine the correlation of personality type and shift work with anxiety level on nurses who work in Emergency Room and Psychiatric Intensive Care Unit in Mental Hospital “X”.Research Method. The type of this study is observational analytic study using a cross sectional design. The number of research subject were 30 people. Independent variables are personality type and shift work. The dependent variable is anxiety level. Variable measurement of shift work were using respondents identity questionnaire. Variable measurement of personality type was using the Bortner scala. Anxiety level measurement was using Hamilton Anxiety Rating Scale (HARS) questionnaires. The effect strength is calculated by using Odds Ratio (OR) from bivariate analysis with logistic regression. Chi square and Fisher test used as significance test. All test used 95% confidence interval and significance level of p 0,05.Result. The result of analysis showed a significant correlation between personality type and shift work with anxiety level on nurses in ER and PICU with with p value 0,03 OR 0,09 (CI 95% 0,01-0,87) dan OR afternoon shift 4,5 (CI 95% 0,63-32,3) dan OR night shift 15,75 (CI 95% 1,75-141,40).Conclusion. There is a significant correlation in personality type and shift work variable with the anxiety level among nurses in ER and PICU Mental Hospital “X”. Keywords. Shift work; anxiety level; nurses.